Effect of weight fraction and particle size of CRT glass on the tribological behaviour of Mg-CRT-BN hybrid composites. (December 2017) - Gopal, P.M.; Soorya Prakash, K.; Nagaraja, S.; Kishore Aravinth, N.
Abstract: The current research focuses on dry sliding wear behaviour of end of life CRT panel glass and BN reinforced hybrid magnesium matrix composite fabricated through powder metallurgy route. CRT panel glass percentage (5, 10 & 15 wt %) and particle size (10, 30 & 50 μm) are varied to find its effect on wear performance and BN solid lubricant is added at a fixed level of 2%. Increase in reinforcement content and particle size decreases the wear rate whereas the opposite trend is found for coefficient of friction. ANOVA results reveal that all of the considered parameters significantly influence the response parameters. Taguchi based GRA is used for multi objective optimization and the worn surface SEM analysis is also performed. Highlights: Development of novel Hybrid Mg MMC with E waste CRT panel glass reinforcement. Effect of reinforcement size and percentage over wear behavior is analyzed. Multi objective optimization though Grey Relational Analysis. Detailed worn out surface analysis through Scanning Electron Microscope.